Spatial, temporal, and demographic patterns in prevalence of smoking tobacco use and attributable disease burden in 204 countries and territories, 1990-2019: a systematic analysis from the Global Burden of Disease Study 2019 - Reitsma, Marissa; Bärnighausen, Till; Chen, Simiao; Jonas, Jost B. (The lancet, 2021)
Background - Ending the global tobacco epidemic is a defining challenge in global health. Timely and comprehensive estimates of the prevalence of smoking tobacco use and attributable disease burden are needed to guide tobacco control efforts nationally and globally. - Methods - We estimated the prevalence of smoking tobacco use and attributable disease burden for 204 countries and territories, by age and sex, from 1990 to 2019 as part of the Global Burden of Diseases, Injuries, and Risk Factors Study. We modelled multiple smoking-related indicators from 3625 nationally representative surveys. We completed systematic reviews and did Bayesian meta-regressions for 36 causally linked health outcomes to estimate non-linear dose-response risk curves for current and former smokers. We used a direct estimation approach to estimate attributable burden, providing more comprehensive estimates of the health effects of smoking than previously available. - Findings - Globally in 2019, 1·14 billion (95% uncertainty interval 1·13-1·16) individuals were current smokers, who consumed 7·41 trillion (7·11-7·74) cigarette-equivalents of tobacco in 2019. Although prevalence of smoking had decreased significantly since 1990 among both males (27·5% [26·5-28·5] reduction) and females (37·7% [35·4-39·9] reduction) aged 15 years and older, population growth has led to a significant increase in the total number of smokers from 0·99 billion (0·98-1·00) in 1990. Globally in 2019, smoking tobacco use accounted for 7·69 million (7·16-8·20) deaths and 200 million (185-214) disability-adjusted life-years, and was the leading risk factor for death among males (20·2% [19·3-21·1] of male deaths). 6·68 million [86·9%] of 7·69 million deaths attributable to smoking tobacco use were among current smokers. - Interpretation - In the absence of intervention, the annual toll of 7·69 million deaths and 200 million disability-adjusted life-years attributable to smoking will increase over the coming decades. Substantial progress in reducing the prevalence of smoking tobacco use has been observed in countries from all regions and at all stages of development, but a large implementation gap remains for tobacco control. Countries have a clear and urgent opportunity to pass strong, evidence-based policies to accelerate reductions in the prevalence of smoking and reap massive health benefits for their citizens. - Funding - Bloomberg Philanthropies and the Bill & Melinda Gates Foundation.
Available online 27 May 2021
Die GBD 2019 Tobacco Collaborators: Marissa B Reitsma, Till Winfried Bärnighausen, Simiao Chen, Jost B Jonas [und weitere]
Gesehen am 26.07.2021